Historical biogeography of Polyura butterflies in the oriental Palaeotropics: trans‐archipelagic routes and South Pacific island hopping. (7th April 2016) - Toussaint, Emmanuel F. A.; Balke, Michael
Abstract: Aim: The respective contribution of vicariance and/or dispersal events to the evolution of clades dwelling in the archipelagic parts of the Oriental and Australian regions remains equivocal. Using a complete, species‐level phylogeny of Polyura butterflies that are widespread in the oriental Palaeotropics, we aim to test predictions related to vicariance driven by past abiotic factors in the Indo‐Australian archipelago (IAA) (Miocene tectonics and Pleistocene climatic shifts) versus repeated trans‐archipelagic dispersal events. Location: The Oriental and Australian regions with a focus on the IAA. Methods: Bayesian species tree phylogenetic analyses were conducted using a matrix comprising two mitochondrial and two nuclear gene fragments. Bayesian relaxed clocks were used to produce a chronogram, which was used in ancestral area estimations to infer the spatio‐temporal evolution of the genus at different geographical scales. Diversification dynamics were investigated using the package Tree Par in R. Results: Polyura originated during the mid‐Miocene ( c . 13 million years ago). Ancestral area estimations inferred an origin in Indomalaya. Wallacea was colonized out‐of‐Indomalaya in the P . pyrrhus group, while the P . athamas and P . eudamippus groups diversified in Indomalaya and the east Palaearctic. We inferred three long‐distance dispersal (LDD) events. The first one implies out‐of‐Sunda colonization of the Solomon Islands, which have three extant, endemic species. The second implies a colonization of Vanuatu out‐of‐Sunda that later served as a stepping stone for the colonization of other Pacific islands (Fiji and New Caledonia). A third permitted the reverse colonization of Wallacea from the Pacific islands. These LDD events were supported by our diversification analyses that suggested no diversification rate shift throughout the evolution of the genus. Main conclusions: Our results suggest unusual colonization routes with Pacific islands as a hub for late Miocene reverse colonizations back into the centre of the Indo‐Australian archipelago.